Degradation of Polycyclic Aromatic Hydrocarbon Pyrene by Biosurfactant-Producing Bacteria Gordonia cholesterolivorans AMP 10 - Tri Handayani Kurniati; Iman Rusmana; Ani Suryani; Nisa Rachmania Mubarik (Biosaintifika: Journal of Biology & Biology Education, 2016)
Pyrene degradation and biosurfactant activity by a new strain identified as Gordonia cholesterolivorans AMP 10 were studied. The strain grew well and produced effective biosurfactants in the presence of glucose, sucrose, and crude oil. The biosurfactants production was detected by the decreased surface tension of the medium and emulsification activity.  Analysis of microbial growth parameters showed that AMP10 grew best at 50 µg mL-1 pyrene concentration, leading to 96 % degradation of pyrene within 7 days. The result of nested PCR analysis revealed that this isolate possessed the nahAc gene which encodes dioxygenase enzyme for initial degradation of Polycyclic Aromatic Hydrocarbon (PAH). Observation of both tensio-active and emulsifying activities indicated that biosurfactants which produced by AMP 10 when grown on glucose could lower the surface tension of medium from 71.3 mN/m to 24.7 mN/m and formed a stable emulsion in used lubricant oil with an emulsification index (E24) of 74%. According to the results, it is suggested that the bacterial isolates G. cholesterolivorans AMP10 are suitable candidates for bioremediation of PAH-contaminated environments.How to CiteKurniati, T. H.,  Rusmana, I. Suryani, A. Mubarik, N. R. (2016). Degradation of Polycyclic Aromatic Hydrocarbon Pyrene by Biosurfactant-Producing Bacteria Gordonia cholesterolivorans AMP 10. Biosaintifika: Journal of Biology Biology Education, 8(3), 336-343.